2015
DOI: 10.1016/j.neuron.2014.12.059
|View full text |Cite|
|
Sign up to set email alerts
|

Barrel Cortex Membrane Potential Dynamics in Social Touch

Abstract: The impact of social stimuli on the membrane potential dynamics of barrel cortex neurons is unknown. We obtained in vivo whole-cell recordings in the barrel cortex of head-restrained rats while they interacted with conspecifics. Social touch was associated with a depolarization and large membrane potential fluctuations locked to the rat's whisking. Both depolarization and membrane potential fluctuations were already observed prior to contact and did not occur during free whisking. This anticipatory pre-contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 27 publications
6
43
0
Order By: Relevance
“…It is an open issue whether the coordination of these motor actions maximizes sensory input [30, 31], such as by sweeping odorants toward the nose. Any source of sensory input that contributes to both touch and olfaction, which are elements of social interactions [32] as well as exploration (Figure 4G), will lead to multisensory input that is likely to be phase-locked to breathing. The temporal regularity of the signals can improve the fidelity of coding of the stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It is an open issue whether the coordination of these motor actions maximizes sensory input [30, 31], such as by sweeping odorants toward the nose. Any source of sensory input that contributes to both touch and olfaction, which are elements of social interactions [32] as well as exploration (Figure 4G), will lead to multisensory input that is likely to be phase-locked to breathing. The temporal regularity of the signals can improve the fidelity of coding of the stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a method for investigating the neural mechanisms underlying song production in a head-fixed context, which represents a rare example of a restrained social behavior (Lenschow and Brecht, 2015; Oomura et al, 1983). Using this approach, we provided population-level support for a notion that HVC projection neurons exhibit an abstract representation of elapsed time, suggesting a scheme for encoding behavior that is divorced from the kinematics of ongoing movements (Lu and Ashe, 2015; Matsuzaka et al, 2007; Tanji and Shima, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Females whisk onto females like a male rat would, but whisk with lower whisking amplitudes onto males 27 . Similar to humans, previous work has shown that even though whisking amplitude is lower during social facial interactions than when investigating objects, population firing rate changes 28 and membrane potential modulations 29 in rat somatosensory cortex are larger during social touch than object touch and do not correlate with whisker movements. Also similar to humans, rat somatosensory activity is modulated in a social context before actual social facial touch 29 and modulation depends on socio-sexual context, such as estrus state 28,30 and emotional state 31 .…”
Section: Introductionmentioning
confidence: 73%